ANALISIS LIMBAH PERCETAKAN TERHADAP DAMPAK PENCEMARAN LINGKUNGAN - Juwairiah; Raju Gobal; Antinah Latif; Pengawet Panjaitan; Ravain Farros, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Printing waste can cause environmental pollution by reducing water quality, which in turn can endanger the health of organisms and ecosystems. The community faces challenges in controlling printing waste due to a lack of understanding of the printing environment, inadequate waste disposal facilities. The aim of the research is to analyze the effect of printing waste on the environment where the research target is the printing area on Jalan Mosque, Kesawan Village, West Medan District. The methods used were surveys, interviews and literature studies carried out using a descriptive approach. This research mostly examines literature sourced from government regulations or legislation, as well as studies from various books. This method is used to plan and manage printing waste, such as burning, sorting, composting, decomposing and recycling. This research design includes a comprehensive literature review and analysis to explore printing waste recycling approaches, their implications, and their potential in driving a sustainable and circular economy.